New Urbanisation and Regional Economic Development: Spatiotemporal Characteristics of County Towns - Hanhui, Liu (Transformations In Business & Economics, 2026)
Inevitably, the Chinese path aims to modernise and integrate urban and rural development to promote the construction of new urbanisation with county towns as important carriers. Using inter-provincial panel data from China from 2006 to 2022, this study employs the “vertical and horizontal segmentation entropy weight method” to scale new urbanisation, with county towns as important carriers. Further, the spatiotemporal characteristics of Chinese new urbanisation, with county towns as important carriers, were analysed using kernel density estimation, the Dagum Gini coefficient, a Markov chain, and a convergence model. The key conclusions are drawn as follows: (ⅰ) The new urbanisation with county towns as important carriers has realised rapid and sustained growth, with a clear spatial pattern of “high in the east, followed by the middle, and low in the west” from the middle and low levels to the middle and high levels; (ⅱ) a certain degree of convergence in the central, western, and national regions exists, whereas the differentiation phenomenon is more pronounced in the eastern region; provinces at low and high levels exhibit a relatively high probability of maintaining their original level; the phenomenon of low-level convergence and high-level convergence clubs is more prominent; (ⅲ) the spatial differences have eased, and the regional differences constitute the core portion of the overall differences, but their contribution is gradually diminishing; (ⅳ) the new urbanisation, with county towns as an important carrier, demonstrates a certain degree of convergence; there are absolute convergence and conditional convergence, however, their speed is relatively slow.